Assessment of technical and scale efficiency of public clinics in eSwatini - Kindandi, Kikanda (Department of Public Health and Family Medicine, 2021)
Developing countries, while working to achieve the WHO universal health coverage goal, have to constantly strike a balance, when allocating their already limited resources, between health and other sectors of their economies (agriculture, education, infrastructure, housing, security, defence etc..). As a result, there is always a limit on how much funding developing countries local governments are able to allocate to their health sector. Limited heath sector funding in the presence of significant health care needs may in turn have a negative impact on health systems outcomes. In addition to government health financing constraints, health systems outcomes in developing countries may also be jeopardized by the prevalence of inefficiencies within local health care delivery systems, especially within public health facilities. This study investigates the level of technical and scale efficiency of a nationally representative sample of 65 randomly selected public clinics in Eswatini using Data Envelopment Analysis. The DEA estimates indicate that 42 clinics (64.7%) were technically inefficient, with an average technical efficiency score of 80.4% (STD= 18.8%). Fifty-one (78.4%) clinics were scale inefficient with an average scale efficiency score of 90.4% (STD = 6.6%). The most prevalent scale inefficiency among public clinics was increasing return to scale with 92.2% (47/51) of scale inefficient clinics operating under increasing return to scale. All 42 inefficient clinics could have delivered the same level of output with 5,701,449.4, US $ less in government funding, 115.3 less clinical staff, 138.8 less support staff and 119.8 less consultation rooms The results reveal inefficiencies within the Health system in Eswatini. It seems possible to save significant amount of money if measures were put in place to mitigate resource wastages. Hence, policy interventions that help not only optimize inputs but also allow outputs expansion through improving the demand for health care would contribute to improving technical and scale efficiency of public clinics in the Kingdom of Eswatini.